Answer:
x = 13
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define equation
-2x + 6 = -20
Step 2: Solve for x
- Subtract 6 on both sides: -2x = -26
- Divide -2 on both sides: x = 13
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: -2(13) + 6 = -20
- Multiply: -26 + 6 = -20
- Add: -20 = -20
Here we see that -20 does indeed equal -20.
∴ x = 13 is the solution to the equation.